Does Improvement of Glycemic Control Cause Acute Charcot Foot in Patients with Diabetes? - Svendsen, Ole Lander; Jansen, Rasmus Bo (Experimental and Clinical Endocrinology & Diabetes, 2025)
Recent studies have suggested that improved glycemic control in patients with diabetes may cause acute Charcot foot. To conduct a narrative review of studies investigating whether improved glycemic control in patients with diabetes causes acute Charcot foot.Publications found by searching PubMed, EMBASE, and Cochrane Library as well as reference lists of identified publications were reviewed.Very few publications were found, primarily consisting of case reports and case studies without control groups, documenting instances where cases of acute Charcot foot had been preceded by improved glycemic control. Recent large multicenter randomized placebo-controlled clinical trials of anti-hyperglycemic agents in patients with diabetes, where significant improvement of glycemic control occurred, have not reported incidences of acute Charcot foot.There is so far no solid evidence to suggest that improvement of glycemic control in patients with diabetes causes acute Charcot foot.
Keywords: diabetes; Charcot foot; glycemic control